Odpowiedź :
Odpowiedź:
a)
[tex] \sqrt{ {3}^{2} } = \sqrt{9} = 3[/tex]
[tex] \sqrt{( - {3})^{2} } = \sqrt{9} = 3[/tex]
[tex] \sqrt[3]{ {3}^{3} } = \sqrt[3]{27} = 3[/tex]
[tex] \sqrt[3]{( { - 3})^{3} } = \sqrt[3]{27} = 3[/tex]
b)
[tex] \sqrt{ {7}^{2} } = \sqrt{49} = 7[/tex]
[tex] \sqrt{( - {7})^{2}} = \sqrt{49} = 7[/tex]
[tex] \sqrt[3]{ {2}^{3} } = \sqrt[3]{8} = 2[/tex]
[tex] \sqrt[3]{( { - 2})^{3} } = \sqrt[3]{8} = 2[/tex]
c)
[tex] \sqrt{ {12}^{2} } = \sqrt{144} = 12[/tex]
[tex] \sqrt{( - {12})^{2} } = \sqrt{144} = 12[/tex]
[tex] \sqrt[3]{ {10}^{3} } = \sqrt[3]{1000} = 10[/tex]
[tex] \sqrt[3]{( { - 10})^{3} } = \sqrt[3]{1000} = 10[/tex]
a)
[tex] \sqrt{ {3}^{2} } = \sqrt{9} = 3[/tex]
[tex] \sqrt[3]{ {3}^{3} } = \sqrt[3]{27} = 3[/tex]
[tex] \sqrt{( { - 3}^{2} )} = \sqrt{9} = 3[/tex]
[tex] \sqrt[3]{( - 3) ^{3} } = \sqrt[3]{ - 27} = - 3[/tex]
b)
[tex] \sqrt{ {7}^{2} } = \sqrt{49} = 7[/tex]
[tex] \sqrt{( { - 7} )^{2} } = \sqrt{49} = 7[/tex]
[tex] \sqrt[3]{2 ^{3} } = \sqrt[3]{8} = 2[/tex]
[tex] \sqrt[3]{( - 2) ^{3} } = \sqrt[3]{ - 8} = - 2[/tex]
c)
[tex] \sqrt{12 ^{2} } = \sqrt{144} = 12[/tex]
[tex] \sqrt{( - 12) ^{2} } = \sqrt{144} = 12[/tex]
[tex] \sqrt[3]{10 ^{3} } = \sqrt{1000} = 10[/tex]
[tex] \sqrt[3]{( - 10) ^{3} } = \sqrt[3] {- 1000} = - 10[/tex]
Myślę że pomogłem ;)